Hubungan status sosial ekonomi dengan perkembangan batita - Rosmita Nuzuliana; Djauhar Ismail; Hikmah Hikmah (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2016)
Abstract: This research aims to determine the relationship socialeconomic status (SES) and other influence factor in the last three monthsdue to child development. We used cross sectional design. SSEindicators were parental level of education, montly family income,parental work . We use identity questionnaires and stimulation ofdevelopment questionnaires, Denver II. Analysis methode by chi-squereand logistic regression for multivariate analysis. Research showed thatthe level of education and occupational status did not affect thedevelopment of toddlers. Affecting factor the development of thetoddlers are parents income, gender, playgroup participation, stimulation.Logistic regresion showed that playgroup participant’s and gender weredominant influence factors for child development.